DOI: 10.33915/etd.3047
|View full text |Cite
|
Sign up to set email alerts
|

Determining efficacy of a thermally processed exogenous enzyme cocktail for broilers

Abstract: Feed ingredient price has influenced nutritionists to maximize diet nutrient availability through use of exogenous enzymes. Poultry are almost exclusively fed pelleted diets that entails feed being subjected to conditions of high moisture, temperature and pressure that could partially denature added enzymes. Exogenous enzyme efficacy may be decreased or completely lost if enzymes are not able to survive the pelleting process. The objective of the current studies was to properly assess the efficacy of a commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, various vitamins and enzymes secreted by B. amyloliquefaciens could increase the digestibility and absorption of nutrients, thereby considerably enhancing growth, in addition to altering the distribution of microorganisms in the gut (Gangadharan, Sivaramakrishnan, Madhavan, & Pandey, ; Telli et al., ). Also,it is well established that supplementation with exogenous enzyme into feed could not only decrease the burden of the environment through recycling of the feed input (Goda, Mabrouk, Wafa, & El‐Afifi, ; Verdegem, ),but also promoting digestion of animals by transforming feed into small molecules (Beaman, ; Bedford, ). Multienzyme complexes are highlighted as a measure that is considered to improve nutrient digestibility to a greater extent than single enzymes (Francesch & Geraert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various vitamins and enzymes secreted by B. amyloliquefaciens could increase the digestibility and absorption of nutrients, thereby considerably enhancing growth, in addition to altering the distribution of microorganisms in the gut (Gangadharan, Sivaramakrishnan, Madhavan, & Pandey, ; Telli et al., ). Also,it is well established that supplementation with exogenous enzyme into feed could not only decrease the burden of the environment through recycling of the feed input (Goda, Mabrouk, Wafa, & El‐Afifi, ; Verdegem, ),but also promoting digestion of animals by transforming feed into small molecules (Beaman, ; Bedford, ). Multienzyme complexes are highlighted as a measure that is considered to improve nutrient digestibility to a greater extent than single enzymes (Francesch & Geraert, ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the thermal conditions of the pelleting process and grinding affected the keratinase recovery and consequent efficacy. Previous research has also shown that feed manufacture can decrease enzyme efficacy [25,26]. show positive effects, however due to decreased activity there were not any significant main effects.…”
Section: Live Bird Performancementioning
confidence: 69%
“…Also, a larger particle size will reduce prehension energy leading to enhanced broiler performance [20]. Although particle size is important, it is found to be more important in mash diets and not pelleted diets [21][22][23][24][25][26][27]. Despite published significant effects of particle size on broiler performance, some literature demonstrates that particle size does not affect performance [22,27].…”
Section: Feed Manufacture Feed Form and Broiler Performancementioning
confidence: 99%